HUBUNGAN INTENSITAS PENGGUNAAN INSTAGRAM TERHADAP INSECURE PADA MAHASISWA - Rahmawati, Rani; Jumaini, Jumaini; Woferst, Rismadefi (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2023)
Introduction: Today's social media is very diverse with different features. Everyone uses social media with different intensity. One of the highest social media used in Indonesia is Instagram. Seeing content uploaded by other Instagram users can make someone feel inferior. Insecure is a form of insecurity. This study aims to determine the relationship between the intensity of Instagram use and insecurity among students at the University of Riau. Methods: This study uses a correlation research design. The sample in this study were 395 respondents who were taken by consecutive sampling technique. The measuring tool used is a questionnaire that has been tested for validity and reliability. The analysis used is descriptive univariate analysis and bivariate analysis, namely the chi square test. Results: The results of the univariate analysis showed that most respondents were in the age range of 20 years (31,9%), were female (71,9%), used Instagram with moderate intensity (56,2%), and most of the respondents experienced insecurity (52,4%). The results of bivariate analysis using the chi square statistical test found a p value of 0,190 with an α value of 0,05. Conclusion: It can be concluded that there is no relationship between the intensity of Instagram use and insecurity among students.